Detecting crack on-set time in mortar prisms with a thermal image - Jong-Gun Park, Gwanghee Heo, Jung Kim, Tetiana Venkel & Jung-Young Son (Nondestructive Testing and Evaluation, 2022)
Thermal images are used to visualise the crack forming processes in mortar prisms under the flexural strength test with a UTM (Universal Testing Machine). The surface temperature of the prisms increases as the stress on them increases. When the prisms are reinforced by carbon fibres, the aggregated fibres along the crack paths becomes distinctive due to their higher temperature compared with their surrounding mortar areas of the prisms. This enables to visualise the crack forming process. In this process, there is a moment of abrupt increase in the temperature gradient of the aggregated fibres. This moment matches closely to that of the crack on-set obtained from the video images of crack forming process taken with a panchromatic camera, with less than 2.2 % difference. The moment is also matched with that of sharp dropping in the force from the UTM after the peak. This sudden temperature gradient increase can be used to determine the crack on-set times of the prisms with a high accuracy.
Keywords: Thermal image, mortar prisms, carbon fibre reinforced, temperature gradient, visualising crack forming process